2009
DOI: 10.1111/j.1439-037x.2009.00387.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Late‐terminal Drought Stress on Yield Components of Four Barley Cultivars

Abstract: Barley (Hordeum vulgare L.) is an important winter cereal crop grown in the semiarid Mediterranean, where late‐terminal drought stress during grain filling has recently become more common. The objectives of this study were to investigate the growth performance and grain yield of four barley cultivars under late‐terminal drought stress under both glasshouse and field conditions. At grain filling, four barley cultivars (Rum, ACSAD176, Athroh and Yarmouk) were exposed to three watering treatments: (1) well‐watere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
131
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(151 citation statements)
references
References 51 publications
19
131
1
Order By: Relevance
“…But the decrease in Rum was lower than that in Yamrouk. Hence, Rum is drought-tolerant whileYarmouk is drought-sensitive (Samarah et al 2009). A significant and similar decrease in growth and photosynthetic activity of the two genotypes was shown when exposed to controlled severe drought at the vegetative stage (Harb & Samarah 2015).…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…But the decrease in Rum was lower than that in Yamrouk. Hence, Rum is drought-tolerant whileYarmouk is drought-sensitive (Samarah et al 2009). A significant and similar decrease in growth and photosynthetic activity of the two genotypes was shown when exposed to controlled severe drought at the vegetative stage (Harb & Samarah 2015).…”
Section: Introductionmentioning
confidence: 64%
“…This suggests that at the molecular level, there are specific drought responses to each genotype. Indeed, Yarmouk genotype was shown to be more droughtsensitive when drought started at the flowering stage than when started at the vegetative stage (Samarah et al 2009;Haddadin et al 2013). Hence, in drought imposed at the vegetative stage different molecular and biochemical responses in the two genotypes result in the same physiological and morphological responses.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown the decreased photosynthetic activity under drought stress due to stomatal or non-stomatal mechanisms (Del Blanco et al, 2000;Samarah et al, 2009). Under drought, the maintenance of leaf turgor may also be achieved by way of osmotic adjustment in response to the accumulation of proline, sucrose, soluble carbohydrates, glycine betaine, and other solutes in cytoplasm thereby improving water uptake from drying soil.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction of stomatal conductance (g s ) and stomatal density is among the remarkable responses to water deicit in alfalfa plants [23,24]. As a consequence of the stomata closure, the difusion of CO 2 from the atmosphere to the carboxylation site is reduced, which inluences the activity of RuBisCO as well as other enzymes such as sucrose phosphate synthase (SPS) and nitrate reductase (NRA), whose inhibition is often considered to be the main cause of the decrease of water-deicient photosynthesis [25]. It has been shown that decreasing water content and ion concentration in water-deicient leaves are more limiting for photosynthesis than closure of stomata [26].…”
Section: Efect On Photosynthesismentioning
confidence: 99%